Haematological profile of children with malaria in Sorong, West Papua, Indonesia - Syilvia Jiero; Ayodhia Pitaloka Pasaribu (Malaria Journal, 2021)
Abstract Background Malaria remains a major public health problem in Indonesian Papua, with children under five years of age being the most affected group. Haematological changes, such as cytopenia that occur during malaria infection have been suggested as potential predictors and can aid in the diagnosis of malaria. This study aimed to assess the haematological alterations associated with malaria infection in children presenting with signs and symptoms of malaria. Methods A retrospective study was performed by collecting data from the medical records of malaria patients at Sorong Regional General Hospital, Sorong, West Papua, Indonesia, both from outpatient and inpatient clinics, from January 2014 until December 2017. The laboratory profile of children suffering from malaria was evaluated. Results One hundred and eighty-two children aged 1 month to 18 years old were enrolled. The subjects were mostly male (112, 61.5%) with a mean age of 6.45 years (SD = 4.3 years). Children below 5 years of age suffered the most from malaria in this study (77, 42.3%). One hundred two subjects (56%) were infected with Plasmodium falciparum. Half of the enrolled subjects (50%) had haemoglobin level (Hb) between 5.1 and 10 gr/dL. A total of 41 children (53.2%) less than 5 years old suffered from P. falciparum infection. In the age group of 5–10 years, there were 34 children (57.6%) who suffered from P. falciparum, and in the age group > 10 years, 27 children (58.7%) suffered from P. falciparum infection. Only 4 subjects (5.2%) in the less than 5 years old age group had mixed malaria infection. Among eight predictors of the haematological profile, there were five predictors that were significantly associated with the diagnostic criteria, namely haemoglobin, haematocrit, leukocytes, platelets and monocytes (p < 0.05). Generally, clinical symptoms are not significantly associated with a malaria diagnosis, and only one variable showed a significant relationship, pale, with a P value of 0.001. Conclusions Children with malaria ...